2024
DOI: 10.1002/adma.202311593
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an Advanced Biomedical Material‐Silk Sericin

Jian Wang,
Huan Liu,
Xiaolei Shi
et al.

Abstract: Sericin, a protein derived from silkworm cocoons, was considered as a waste product derived from silk industry for thousands of years due to a lack of understanding of its properties. However, in recent decades, a range of exciting properties of sericin have been studied and uncovered, including cytocompatibility, low‐immunogenicity, photo‐luminescence, antioxidant properties, as well as cell‐function regulating activities. These properties make sericin‐based biomaterials promising candidates for biomedical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 183 publications
(164 reference statements)
0
0
0
Order By: Relevance
“…Our results agree with the results reported by Tariq et al [ 44 ], who demonstrated the wound healing effects of sericin in diabetic mice; further studies demonstrated that sericin increased cell attachment and migration, the proliferation of keratinocytes and fibroblasts, and collagen synthesis, thus promoting wound healing in humans without the production of pro-inflammatory cytokines [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results agree with the results reported by Tariq et al [ 44 ], who demonstrated the wound healing effects of sericin in diabetic mice; further studies demonstrated that sericin increased cell attachment and migration, the proliferation of keratinocytes and fibroblasts, and collagen synthesis, thus promoting wound healing in humans without the production of pro-inflammatory cytokines [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultssupporting
confidence: 93%
“…EpiDermFT TM tissues (EFT-412) were provided from the MatTek Corporation (Ashland, MA, USA); Dulbecco's Modified Eagle (DMEM)-based medium for maintaining cultures was supplied by the manufacturer (EFT-400-MM). Anti-Cytokeratin 14 antibody, Our results agree with the results reported by Tariq et al [44], who demonstrated the wound healing effects of sericin in diabetic mice; further studies demonstrated that sericin increased cell attachment and migration, the proliferation of keratinocytes and fibroblasts, and collagen synthesis, thus promoting wound healing in humans without the production of pro-inflammatory cytokines [45][46][47][48][49].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is considered not only to be a key component of traditional medicine but also a crucial material in contemporary medical innovation. Presently, its applications primarily manifest in areas such as drug delivery systems [24][25][26], tissue engineering [27][28][29][30], and regenerative medicine [30,31]. These studies leverage the biodegradability and excellent biocompatibility of SC to develop new medical materials and treatment methods, showcasing its potential as a natural resource in the contemporary medical domain.…”
Section: Introductionmentioning
confidence: 99%